Emotional Education Discourses: Between Developing Competences and Deepening Emotional (Co-)Understanding - Góralska, Renata (Qualitative Sociology Review, 2020)
The article addresses an issue important in educational sciences which is emotional education understood as an activity for human emotional development. It is important in the context of lifelong learning, that is, both for the functioning of children and young people at school and for the lifelong learning of adults. Emotional education plays a significant role in the development of pro-social attitudes, the functioning of individuals in the local community, and in the building of civil society. Owing to the fact that the objectives of education and the principles of their implementation in educational practice are based on different theoretical assumptions, two different approaches to emotional education were distinguished, that is, technological-instrumental and humanistic-critical. There are clear and significant differences between those two perspectives, and not only in the way they conceptualize and explain “emotional education.” The two singled out approaches have consequences for educational policy and pedagogical practice. The aim of the article is to characterize both of the theoretical perspectives at hand and to indicate their implications for pedagogical activities.